Feminist constitutionalism : global perspectives - Baines, Beverley, 1941-; Barak-Erez, Daphne; Kahana, Tsvi, 1967- (Cambridge : Cambridge University Press, 2012)
'This book aims to explore the relationship between constitutional law and feminism. The contributors offer a spectrum of approaches and the analysis is set across a wide range of topics, including both familiar ones like reproductive rights and marital status and emerging issues such as new approaches to household labor and participation of women in constitutional discussions online. The book is divided into five [sic] parts: I) feminism as a challenge to constitutional theory; II) feminism and judging; III) feminism, democracy and political participation; IV) the constitutionalism of reproductive rights; V) women's right, multiculturalism, and diversity; and VI) women between secularism and religion. As a collection, the book seeks to examine, challenge, and indeed redefine the very idea of consitiutionalism from a feminist perspective'--
Includes bibliographical references and index.
Keywords: Women's rights; Constitutional law; Feminist jurisprudence